2014
DOI: 10.1182/blood-2013-08-520387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multiple platelet activation pathways in patients with bleeding as a high-throughput screening option: use of 96-well Optimul assay

Abstract: Key Points The Optimul 96-well platelet aggregation assay has high levels of sensitivity and specificity for detecting platelet defects. The requirement for a small volume of blood, straightforward nature, and speed make Optimul a promising screening test in bleeding patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…A total of 2.5 ml PRP is needed to compare all agonist concentrations on the plate, which is the equivalent of approximately 6 ml blood compared to the approximate 50 ml that would be required to produce the same analysis through LTA (32). The low blood volume required makes this method of particular benefit in cases where blood sample is limited, such as in patients with advanced disease and in neonates.…”
Section: Lyophilized Agonist Platelet Aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2.5 ml PRP is needed to compare all agonist concentrations on the plate, which is the equivalent of approximately 6 ml blood compared to the approximate 50 ml that would be required to produce the same analysis through LTA (32). The low blood volume required makes this method of particular benefit in cases where blood sample is limited, such as in patients with advanced disease and in neonates.…”
Section: Lyophilized Agonist Platelet Aggregationmentioning
confidence: 99%
“…We and others, however, have demonstrated that the effect of anti-platelet drugs can be elucidated using this method (18,31,32). …”
Section: Lyophilized Agonist Platelet Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…As all other parameters were identical these differences can only be explained by differences in the mechanical/physical environments of the two assays (3). LTA is fairly standardized with respect to the mixing of platelets with a stirrer bar turning at 1000–1200rpm.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, the Optimul system relies on optical measurement of sample turbidity to assess platelet aggregation, making it unsuitable for analysis of platelet function in whole blood. Several studies have demonstrated platelet counting to be a viable alternative method for monitoring platelet aggregation because single platelets are "consumed" into larger aggregates upon activation.…”
Section: Introductionmentioning
confidence: 99%